Mind-mapping for conceptual material of introduction to management - Kartikowati, Rr. Sri; Gimin, Gimin; Sakdanur, Sakdanur (Journal of Educational Sciences, 2018)
Students with difficulty in comprehending conceptual materialsneed media that has powers in organizational, procedural visual, andsupporting creative thinking; all are integrated in a mind-mapping media.This research is aimed to develop a learning design of Introduction toManagement based on mind-mapping media concerning with conceptualmaterials. This is an early phase of research and development activities, inIntroduction to Management class. Data of needs analysis is obtainedthrough survey technique on 38 college students, then followed by literaturestudy and focus group discussions. The result shows that a learning designof Introduction to Management, that highlights conceptual materials, hasconstructed on the basis of mind-mapping media. The design consisted oflearning outcome, stages of preparing mind mapping media, andmeasurement method of effectiveness of the learning designimplementation.